Pengaruh Subtitusi Abu Kayu Terhadap Semen Ditinjau Dari Kuat Tekan dan Kuat Tarik Belah Beton - Azhar Azhar; Jasman Jasman; Hamka Hamka (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Concrete is a rock made from a mixture of cement, sand, aggregate and water. For this reason, this construction material is very important to develop. One effort to develop it is by utilizing industrial waste. Like other industrial waste, wood ash waste can also be used as a partial replacement for cement. The aim of this research is to determine the effect of adding wood ash as an additive to cement on the compressive strength and tensile strength of concrete, as well as to determine the effect of varying the percentage of wood ash in the concrete mixture on the compressive strength and split tensile strength of concrete. The type of research used in this research is quantitative research with experimental methods, namely by comparing normal concrete with 3 variations of mixture to determine the compressive strength and splitting tensile strength of the concrete. The results of the research showed that the experimental compressive strength and split tensile strength of concrete on normal concrete and variations of 3 mixtures, namely 2%, 4% and 6% of cement, obtained experimental results on the compressive strength of concrete for 28 days of normal concrete with an average of the average of 25,478 Mpa decreased with a 2% variation with an average of 24,723 Mpa, and decreased drastically for a 4% variation with an average of 19,439 Mpa, and for a 6% variation with an average of 18,967 MPa. Meanwhile, in testing the split tensile strength of normal concrete with an average of 7.185 Mpa, it experienced an increase from normal concrete with a variation of 2% with an average of 7.333 Mpa, and experienced a decrease from normal concrete with a variation of 4% with an average of 6.667 Mpa, and 6%. with an average of 6 Mpa. So it can be concluded that concrete with a variation of 2% wood ash does not really affect the compressive strength of the concrete, but the more wood ash that is added, the compressive strength of the concrete will decrease. From this research it can be concluded that the use of wood ash does not achieve the planned compressive strength so it is not suitable for use in construction.